ASUHAN KEPERAWATAN PADA KLIEN ASMA KRONIKDENGAN MASALAH BERSIHAN JALAN NAPAS TIDAKEFEKTIF - Apriliana (2023)
Ineffective airway clearance is the inability to clear secretions or airway obstruction to maintain a patent airway, which usually occurs in asthmatic patients. Ineffective airway clearance in asthma can occur due to shortness of breath, coughing, rhonchi or wheezing, causing airway spasm. The purpose of this study was to carry out nursing care for clients with chronic asthma with ineffective airway clearance problems in Sasak Limo Village, Depok. The method used in this research is descriptive method in a case study approach on one asthmatic client. Nursing care is carried out for 3x24 hours, it is hoped that the road cleaning problem can be resolved, by showing decreased shortness of breath, increased effective cough, decreased sputum production, decreased crackles, increased respiratory frequency, improved breathing patterns. Clients show changes in shortness of breath with reduced shortness of breath, cough effective increase, there are no crackles, respiratory rate 20 x/minute. The provision of nursing care that has been given is effective in overcoming the problem of ineffective airway clearance, especially in the semi-Fowler's position and effective coughing in asthma sufferers.